Leaf dynamics and maintenance of tree crowns in a Malaysian rain forest stand - Osada, Noriyuki; Takeda, Hiroshi; Furukawa, Akio; Awang, Muhamad (Wiley, 2001)
1 Leaf demography was examined for trees of various heights over a 3.7-year period in a Malaysian rain forest. We compared demography between upper and lower parts of the crown and its relation to height. The results were analysed at the stand level by pooling several trees of various shade-tolerant species, as well as three species for which multiple individuals were sampled.